2020
DOI: 10.1038/s41467-020-18867-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for energy transfer in a huge diatom PSI-FCPI supercomplex

Abstract: Diatom is an important group of marine algae and contributes to around 20% of the global photosynthetic carbon fixation. Photosystem I (PSI) of diatoms is associated with a large number of fucoxanthin-chlorophyll a/c proteins (FCPIs). We report the structure of PSI-FCPI from a diatom Chaetoceros gracilis at 2.38 Å resolution by single-particle cryo-electron microscopy. PSI-FCPI is a monomeric supercomplex consisting of 12 core and 24 antenna subunits (FCPIs), and 326 chlorophylls a, 34 chlorophylls c, 102 fuco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(152 citation statements)
references
References 54 publications
6
141
3
2
Order By: Relevance
“…Dissolved FCP crystals excite at 436, 465, and 540 nm and the fluorescence emission wavelength is 676 nm [16]. The fluorescence spectrum scan of PSI-FCPI showed that there is a single emission wavelength at about 708 nm, which is similar to our results [27]. The fluorescence emission spectra of PSII-FCPII excite at 425, 459, and 500 nm, measuring at 77 K. The main peak is located at 694 nm [28,29].…”
Section: P Tricornutum Has a Specific Emission Wavelengthsupporting
confidence: 88%
See 1 more Smart Citation
“…Dissolved FCP crystals excite at 436, 465, and 540 nm and the fluorescence emission wavelength is 676 nm [16]. The fluorescence spectrum scan of PSI-FCPI showed that there is a single emission wavelength at about 708 nm, which is similar to our results [27]. The fluorescence emission spectra of PSII-FCPII excite at 425, 459, and 500 nm, measuring at 77 K. The main peak is located at 694 nm [28,29].…”
Section: P Tricornutum Has a Specific Emission Wavelengthsupporting
confidence: 88%
“…These results illustrate that the emission fluorescence of P. tricornutum cells at 710 nm should not be emitted by a single pigment and is most likely a special fluorescence emission peak of the photosynthetic system complex structure in diatoms. In recent reports, the structures of FCP complex, PSI-FCPI, and PSII-FCPII were analyzed by cryo-electron microscopy [16,[27][28][29]. In the separation and purification of these complex structures, fluorescence emission spectra at 77 K were measured using a fluorescence spectrophotometer.…”
Section: P Tricornutum Has a Specific Emission Wavelengthmentioning
confidence: 99%
“…In contrast, PSI cores from eukaryotic algae and higher plants exist as a monomer, which is associated with various membrane-spanning light-harvesting complex I (LHCI), forming PSI–LHCI supercomplexes. The structures of PSI–LHCI supercomplexes have been solved from various eukaryotic organisms such as red algae 6 , diatoms 7 , 8 , green algae 9 11 , and land plants 12 14 . These studies showed that the PSI core is relatively conserved during more than 2.5 billion years of evolution, whereas there is a large diversity in the pigment and protein compositions of LHCI from different organisms 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of PSI‐LHCI supercomplex from higher plants was also analyzed at 2.6–2.8 Å resolutions (Mazor et al, 2015, 2017; Qin et al, 2015; Pan et al, 2018). Recently, the structure of PSI‐LHCI from a red alga (Antoshvili et al, 2018; Pi et al, 2018), a diatom (Nagao et al, 2020; Xu et al, 2020) and green algae (Qin et al, 2019; Su et al, 2019; Suga et al, 2019) have been solved by cryo‐EM. These studies revealed that the cofactor arrangement of the PSI core involved in electron transfer is highly conserved from cyanobacteria to higher plants, which occurs in two branches of the core beginning from P 700 to primary and secondary electron acceptors A Acc , A 0 , A 1 , and finally to the three Fe 4 S 4 clusters (Nelson and Junge, 2015).…”
Section: Introductionmentioning
confidence: 99%